PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN LITERASI NUMERASI SISWA - Saphyra, Aura; Usman; Dwi Fadhiliani (Universitas Insan Budi Utomo, 2026)
Numerical literacy is a crucial aspect of mathematics education in high school. However, a common issue is the low numerical literacy skills among students. One model that can be applied to improve students' numeracy literacy skills is the Problem Based Learning model (PBL). This study aims to investigate the influence of the PBL model on the numerical literacy skills of high school students, specifically in the topic of sequences and series. The research used a quantitative approach with a quasi-experimental design and a nonequivalent group design. The population for this study was all students in grade XI Social Sciences at SMA Negeri 1 Teunom. The research sample was selected using a total sampling technique, with one class designated as the experimental group and another as the control group. Data were collected using a numerical literacy test instrument in the form of essay questions on sequences and series. The data analysis was performed using the Mann-Whitney U test. The results show that students who learned using the PBL model had better numerical literacy skills compared to those who learned using a conventional teaching model. Therefore, the Problem Based Learning (PBL) model is recommended for teachers to improve students' numerical literacy skills.